Zero-waste biomass gasification: Use of residues after gasification of bagasse pellets as CO2 adsorbents. (1st December 2021) - Nguyen, Hong Nam; Nguyen, Phuong L.T.; Tran, Van Bay
Highlights: The 20 kWe -gasification system worked smoothly with sugarcane bagasse pellets. A complete database regarding characteristics of residues after gasification was provided. The optimum CO2 adsorption performance of residues reached 2.8 mmol g −1 at 25 °C, exceeding a wide range of other adsorbents. Great potential for use of residues after gasification as cheap and efficient CO2 adsorbents. Abstract: Biomass gasification is a prominent technology for energy production at small and medium scales, especially in developing countries where biomass feedstock is abundantly available. The expansion of this technology, however, has been hindered due to the low conversion efficiency, generating important amounts of solid waste after the process. Finding suitable applications for residues after gasification is thus crucial for the sustainable development of this technology. This study investigated the characteristics of the residues after gasification of bagasse pellets on a semi-industrial scale gasifier and their potential for use as CO2 adsorbents. Results indicated a smooth operation of the 20 kWe -gasification system (PP20 - All Power Lab) with the new feedstock. The residues after gasification taken at different locations showed heterogeneity in terms of physicochemical characteristics and morphology, but still contained high carbon content and diverse carbon structure. The high specific surface area and pore volume of some residues are comparable with commercial activated carbon products. The optimum CO2 adsorption performance was 2.8 mmol g −1 at 25 °C, which exceeded a wide range of other adsorbents. Under extreme industrial conditions (100 °C, 15% CO2 in N2 ), the CO2 capture capacity still reached 2.6 wt% of adsorbent, thereby proving the great potential for use of residues after bagasse gasification as CO2 adsorbents in practice. The result would contribute to an idea for a "zero-waste" gasification system and a sustainable approach for the production of CO2 adsorbents.